Biological activities of the protein hydrolysate obtained from two fishes common in the fisheries bycatch. (16th April 2021) - Rocha Camargo, Tavani; Ramos, Patrícia; Monserrat, José M.; Prentice, Carlos; Fernandes, Célio J.C.; Zambuzzi, Willian F.; Valenti, Wagner C.
Graphical abstract: Highlights: Some fishes from bycatch can be sources of protein hydrolysates for industry. The protein hydrolysates obtained from two fish species have antioxidant properties. Protein hydrolysates showed no cellular toxicity at doses lower than 16 mg/mL. Protein hydrolysates can modulate extra and intracellular pathways of cell adhesion. Abstract: Shrimp trawling is an important socio-economic activity; however, the bycatch can be problematic to the environment. Thus, the present study investigated potential uses of the bycatch to generate value-added products. The biological activity of the protein hydrolysates obtained from the two most abundant fish species ( Micropogonias furnieri and Paralonchurus brasiliensis ) was evaluated. Muscle and skin samples of both species were hydrolyzed using two enzymes, Alcalase 2.4 L® or Protamex®. The in vitro antioxidant capacity against peroxyl radicals, DPPH, and sulfhydryl groups were analyzed. Cell viability, Western Blotting, Zymogram, and Real-time PCR analyses were performed. The results showed that the hydrolysates have antioxidant activity and no effect on cell viability at doses lower than 16 mg/mL. In addition, they can modulate extracellular remodelling and intracellular pathways related to cell adhesion. Thus, the hydrolysis of the fish bycatch allows the release of bioactive peptides with potential use in the food industry.